Theranostic nanoemulsions suppress macrophage-mediated acute inflammation in rats - Riddhi Vichare; Yalcin Kulahci; Rebecca McCallin; Fatih Zor; Fatma Nurefsan Selek; Lu Liu; Caitlin Crelli; Anneliese Troidle; Michele Herneisey; James M. Nichols; Andrew J. Shepherd; Vijay S. Gorantla; et al. (Journal of Nanobiotechnology)
Abstract In inflammatory diseases or following an injury, dysregulated inflammation is a common driver of pain and tissue damage. Macrophages are immune cells that contribute to the initiation, maintenance, and resolution of inflammation due to their phenotypic plasticity in response to signals from inflammatory microenvironments. Macrophages infiltrate and polarize toward a pro-inflammatory phenotype (M1-like), thereby increasing the severity of inflammation. Therefore, we aimed to suppress the pro-inflammatory activity of M1-like macrophages and decrease their infiltration at the site of inflammatory insult to resolve tissue inflammation. To achieve this, we developed a theranostic curcumin-loaded nanoemulsion platform that delivers a low dose of curcumin, a known anti-inflammatory phytochemical, to macrophages and allows in vivo tracking of macrophages by near-infrared fluorescence (NIRF) imaging technique. In vitro, we showed that curcumin-loaded nanoemulsion suppressed polarization of macrophages towards M1-like phenotype, consequently decreasing the release of pro-inflammatory cytokines and mediators like IL-6, IL- $$\:β\:,$$ TNF- $$\:α\:$$ , and nitric oxide (NO). Furthermore, curcumin-loaded nanoemulsion increased the level of IL-10, an anti-inflammatory cytokine, and protected macrophages against ferroptosis compared to drug-free nanoemulsion. In a rodent model of Complete Freund’s adjuvant (CFA)-induced inflammation, we demonstrated that infiltrating macrophages sequestered curcumin-loaded nanoemulsion droplets and acted as cellular drug depots at the site of inflammation. This consequently decreased macrophage infiltration at the CFA-induced inflammation site in both sexes compared to drug-free nanoemulsion, as demonstrated by NIRF imaging, H&E staining, and immunofluorescence. Taken together, our results indicated that the anti-inflammatory efficacy of curcumin was significantly improved when directly delivered to pro-inflammatory macrophages via theranostic nanoemulsion. This work opens an avenue for exploring theranostic nanoemulsions as a platform for delivering natural anti-inflammatory products for immune modulation. Graphical abstract